ANTIBIOTIC SUSCEPTIBILITY TESTING FOR ESCHERICHIA COLI CAUSING URINARY TRACT INFECTIONS IN SOKOTO METROPOLIS - Umar, Muhammad Nura; Mustapha, Bature; Tanko, Nuhu; Aminu, Nafiu (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The study was designed to diffuse awareness on the prevalence of Escherichia coli as a causative agent of urinary tract infection (UTI) in Sokoto metropolis as well as to determine the susceptibility to commonly used antibiotics in Specialist Hospital Sokoto (SHS). This is also to raise awareness of the risk of giving antibiotics and their direct impact on the outcome analysis of UTIs. Methods: This study was conducted at SHS, and ethical approval to carry out the study was obtained from the Ethical Committee of the hospital. Informed consent was obtained from each participant. Early morning, mid-stream clean catch urine samples were collected by patients in sterile disposable containers. The antibiotic susceptibility of the isolates was determined against 10 commonly prescribed antibiotics in SHS using the modified Kirby–Bauer disc agar diffusion. Results: A total of 86 urine samples were analyzed over 2 months, and 34 were culture positive giving an isolation rate of 39.5%, while 48 were culture negative giving a rate of 55.8%, and 4 (4.7%) were undecided. A total of 16 isolates were E. coli (47.1%), while 18 accounts for others (52.9%). The results of antimicrobial susceptibility profile to 10 antibiotics showed that E. coli displayed high susceptibility to vancomycin (91.6%), followed by amikacin (89.2%) and then meropenem (88.0%), while high rate of resistance was found in nalidixic acid (81.2%), followed by co-trimoxazole (73.3%) and then norfloxacin (76.2%). Conclusion: When there is an adequate detection of E. coli and other uropathogens, it will aid in selecting the appropriate antimicrobial therapy and this will also serve as a means of infection control. This will go a long way in reducing the cost of treatment and threat of resistance as witnessed in the management of some uropathogens.